Bleeding Risk Associated with Resection of the Middle Turbinate during Functional Endoscopic Sinus Surgery. Issue 2 (March 2016) - Miller, Anya J.; Bobian, Michael; Peterson, Ed; Deeb, Robert
Background: The decision to resect the middle turbinate (MT) during functional endoscopic sinus surgery is controversial. Although there have been a variety of studies that examined the functional outcome related to this maneuver, very few studies evaluated the potential for complications, in particular, epistaxis. Objective: We sought to determine ifresection of the MT during functional endoscopic sinus surgery leads to an increased risk for postoperative bleeding. Methods: Patients who underwent functional endoscopic sinus surgery for chronic sinusitis or nasal polyposis between 2004 and 2014 at a single institution were analyzed for bleeding and other complications after resection of the MT. Results: Between 2004 and 2014, 1185 sinus surgeries were performed by 18 surgeons. A propensity matched set of 228 patients who underwent turbinate resection, and 228 controls were selected based on predicted probabilities from a logistic regression that predicted turbinate resection and that was adjusted for age, sex, and procedure. There were 89 patients with bilateral turbinates removed and 139 with unilateral turbinates removed. There was no significant difference in major bleeding or other complication rates between the two groups. Patients who underwent resection of at least one MT were 3.95 times more likely to have minor bleeding compared with those who did not; this risk increased with the number of turbinates resected (trend p = 0.008). Patients on anticoagulation medications were at a significant risk of bleeding if their MT was removed (p = 0.007), whereas patients on aspirin or antiplatelet therapy were not at a significant risk. Conclusion: There was no increased risk of major bleeding or other complication associated with resection of the MT. However, there was a significantly increased minor bleeding rate associated with MT resection, particularly ifthe patient was on anticoagulants.